Predictors of recovery from post-deployment posttraumatic stress disorder symptoms in war veterans: The contributions of psychological flexibility, mindfulness, and self-compassion. (March 2019) - Meyer, Eric C.; Szabo, Yvette Z.; Frankfurt, Sheila B.; Kimbrel, Nathan A.; DeBeer, Bryann B.; Morissette, Sandra B.
Abstract: Posttraumatic stress disorder (PTSD) is a major challenge among war veterans. This study assessed the contribution of several interrelated, modifiable psychosocial factors to changes in PTSD symptom severity among combat-deployed post-9/11 Veterans. Data were drawn from a longitudinal study of predictors of mental health and functional outcomes among U.S. Iraq and Afghanistan war Veterans ( N  = 117). This study assessed the unique contribution of psychological flexibility, mindfulness, and self-compassion to PTSD recovery, after accounting for established predictors of PTSD chronicity, including combat exposure, alcohol use problems, and traumatic brain injury. PTSD symptom severity was assessed using a clinician-administered interview, and PTSD recovery was defined as the change in symptom severity from lifetime worst severity, measured at baseline, to current severity at one-year follow-up. A mindful awareness latent factor comprised of all three variables measured at baseline predicted PTSD recovery beyond the other predictors of PTSD chronicity ( f 2  = 0.30, large effect). Each construct predicted PTSD recovery when tested individually. When tested simultaneously, self-compassion, but not mindfulness or psychological flexibility, predicted PTSD recovery. These findings suggest that mindful awareness of emotional distress predicts recovery from PTSD symptoms in war veterans, which supports the utility mindfulness-based interventions in promoting post-trauma recovery. Highlights: A psychological flexibility-self-compassion-mindfulness factor predicted recovery. In sensitivity analyses, each individual construct predicted PTSD recovery. Bolstering these skills would likely promote recovery from PTSD symptoms. Mindful attitudes predicted PTSD recovery over established predictors of chronicity.